The Effect of Stiffeners and Castellated Beam Hole Covers on Buckling in Ramp Door Construction with Finite Elemen Method - Abdul Hari Nugroho; Pio Ranap Tua Naibaho (Jurnal Infrastruktur, 2025)
Castellated steel is a steel beam that has a hexagonal hollow web element. One of the cases that often occurs in castellated steel structures is buckling. This study takes a case study of ramp door construction made of castellated steel. The ramp door construction experienced buckling damage after a load test. Analysis was carried out on four ramp door models with loading resembling the actual conditions of the bridge according to SNI 1725-2016. The first modeling uses a 900x200x11x17 castellated main beam without the addition of stiffeners. The second modeling with the addition of stiffeners at each distance between castellated holes. The third modeling closes all holes without the addition of stiffeners. The fourth modeling closes all holes with the addition of stiffeners at each distance between castellated holes. The analysis was carried out using the finite element method. This study aims to determine the effect of stiffeners and castellated hole covers on deformation values, equivalent stress and buckling eigenvalues. From the analysis of the effect of stiffener (second model) for the deflection value decreased by 0.62%, the stress value increased by 4.04%, the buckling eigenvalue increased by 144.94%. The effect of castellated cover (third model) for the deflection value decreased by 8.69%, the stress value decreased by 19.71%, the buckling eigenvalue increased by 12.75%. The effect of stiffener and castellated cover (fourth model) for the deflection value decreased by 11.18%, the stress value decreased by 20.15%, the buckling eigenvalue increased by 153.98%.